2016
DOI: 10.1177/0950017015590759
|View full text |Cite
|
Sign up to set email alerts
|

Safety at the workplace: accidents and illnesses

Abstract: The topic of work safety is a very relevant and multifaceted problem for workers, firms and policy makers. Differing from other narrow scope studies, this article aims to enrich the understanding of workplace safety as a whole by applying econometric techniques on data from the Italian Labour Force Survey. Findings show poor working conditions are the most significant determinants of accidents and illnesses occurring at work while having a fixed-term (temporary) contract is not significant. Other significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
2
14
0
2
Order By: Relevance
“…In such cases we consider the actual bad working conditions to mirror the perceived bad working conditions, with no expectation mechanism at work. These results are in line with some theoretical predictions (Khanzode et al, 2012) and some empirical contributions (Cioni and Savioli, 2016) underlining that expanding the working time (such as being a full-time worker, working overtime hours and engaging in shift work), ceteris paribus, increases the chance of accidents and illnesses.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In such cases we consider the actual bad working conditions to mirror the perceived bad working conditions, with no expectation mechanism at work. These results are in line with some theoretical predictions (Khanzode et al, 2012) and some empirical contributions (Cioni and Savioli, 2016) underlining that expanding the working time (such as being a full-time worker, working overtime hours and engaging in shift work), ceteris paribus, increases the chance of accidents and illnesses.…”
Section: Discussionsupporting
confidence: 89%
“…In the past decades, labour economics research has demonstrated the influence of working conditions on a number of issues, such as the probability of experiencing job accidents and illnesses in the workplace as well as workers' job satisfaction, health and quality of life more generally. For instance, a recent article on work safety by Cioni and Savioli (2016) highlights that poor working conditions are among the major determinants of accidents and illnesses at work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a substantive review of the literature on dangerous and extreme work contexts agrees that this disparate body of research is hugely fragmented (Hällgren et al, 2018). Relevant fields include risk management, health and safety, and workplace well-being (Cioni and Savioli, 2016; Perrow, 1984). Danger can also feature intermittently in relation to dirty, precarious or stigmatised forms of work (Ashforth and Kreiner, 1999; Standing, 2016), and violence and bullying (Costas and Grey, 2018; Simpson and Cohen, 2004).…”
Section: Solidarity In Dangerous Work and Edgeworkmentioning
confidence: 99%
“…In underground coal mines, working condition and geological disturbance related hazards are very prominent [14][15][16][17] . At a continuous miner worksite, production is achieved with the help of robust machines.…”
Section: Introductionmentioning
confidence: 99%